2019
DOI: 10.1002/hpm.2770
|View full text |Cite
|
Sign up to set email alerts
|

Elements of community‐based models for treating hepatitis C virus in supporting HCV elimination in Australia: A Delphi study

Abstract: Summary Background A key to achieving the goal of hepatitis C virus (HCV) elimination is the provision of its treatment in community settings. This study aimed to identify the important organisational and operational elements of community‐based models for treating HCV and their feasibility in the Australian context. Methods A Delphi study was conducted with 33 experts from Australia. The questionnaire included 13 elements drawn from the literature. Participants rated each element on a five‐point Likert scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…This was also reported in other studies as a barrier to HCV treatment . Enabling PCPs to assess patients’ psychosocial status and empowering them to provide support for patients through collaboration or linkage with other related services are essential to successfully engage PCPs in HCV treatment …”
Section: Discussionsupporting
confidence: 55%
“…This was also reported in other studies as a barrier to HCV treatment . Enabling PCPs to assess patients’ psychosocial status and empowering them to provide support for patients through collaboration or linkage with other related services are essential to successfully engage PCPs in HCV treatment …”
Section: Discussionsupporting
confidence: 55%
“…This nurse-led model of care incorporates all eight elements identified by consensus as being important for community-based hepatitis C treatment. 19 These elements include; a safe and enabling environment, training and support for health care providers, an open referral policy, linkage with or providing outreach services, a person-centred approach, on-site screening and assessment, linkage or co-location with harm reduction services and linkage or co-location with drug and alcohol services. These elements are important in expanding access to HCV treatment with prescribing limited to specialist clinicians in other settings globally.…”
Section: Discussionmentioning
confidence: 99%
“…Third, barriers to being referred to a hospital included a high percentage of patients who were unable to be contacted, the patients' self-perception of being healthy, mistrust of treatment/ healthcare, transportation issues, and work conflict. Recently, in Australia, Pourmarzi et al [18] demonstrated that a key to achieving the HCV elimination goal is the provision of its treatment in community settings, and that the integration and coordination of care and support provided for both patients and healthcare providers are important processes. The present study lends support to Pourmarzi et al [18], who reported that successful elements of treatment in community settings include "training and support for healthcare providers, an open referral policy, linkage with or providing outreach services, a person-centered approach, and on-site screening and assessment."…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in Australia, Pourmarzi et al [18] demonstrated that a key to achieving the HCV elimination goal is the provision of its treatment in community settings, and that the integration and coordination of care and support provided for both patients and healthcare providers are important processes. The present study lends support to Pourmarzi et al [18], who reported that successful elements of treatment in community settings include "training and support for healthcare providers, an open referral policy, linkage with or providing outreach services, a person-centered approach, and on-site screening and assessment." Further, to increase access to treatment for HCV in Australia, White et al [19] developed a community-based FibroScan and a nurse-led service to assess patients.…”
Section: Discussionmentioning
confidence: 99%